Comparison between radiography and computed tomography for diagnosis of equine skull fractures. (27th November 2017) - Crijns, C. P.; Weller, R.; Vlaminck, L.; Verschooten, F.; Schauvliege, S.; Powell, S. E.; van Bree, H. J. J.; Gielen, I. M. V. L.
Summary: The equine head is a complex structure prone to traumatic injuries. To determine the value and limitations of radiography and (CT) for the diagnosis of skull fracture, the differences between the two modalities were described. Two observers retrospectively reviewed the radiographic and CT images of 18 horses with a skull fracture. To allow direct comparison between the two modalities, a simplified fracture classification system was used. In 3/18 cases the evaluation of the radiographic examination concluded no injuries visible. In 2/15 cases soft tissue involvement was not detected and in 7/15 cases the extension of the fracture was underestimated with radiography. Radiography classified 4/10 multiple fractures incorrectly as single fracture and 5/15 comminuted fractures on CT were diagnosed as simple fracture with radiography. The number of fragments was underestimated with radiography in 14/15 cases. In conclusion, radiography is able to diagnose a skull fracture in most cases. Skull fractures however are not similarly classified after radiographic and CT evaluation, which causes a difference in interpretation and perception of the fractures. Therefore, CT should be the modality of choice for surgical planning and prognosis.